A Modified Hockett-Sherby Law Enabling the Description of the Thermomechanical Behaviour of the AA6061-T6 - Oliveira, Marta C. (2020)
The use of warm temperatures in the forming process enhances the aluminium alloys formability and reduces the springback effect, when compared with room temperature conditions. However, in order to be able to design warm forming processes it is necessary to describe the influence of temperature and strain rate on the mechanical behaviour of the material. This work presents the procedure adopted to identify the parameters of a thermomechanical Hockett-Sherby type law, for the EN AW 6061-T6 aluminium alloy, based on previously reported results from experimental uniaxial tensile tests performed on a Gleeble machine [1]. The experimental data were analysed, in order to obtain the true stress-plastic strain curves, for a temperature range between room temperature and 200°C, at three different strain rates. A classical identification procedure was applied to identify the parameters of a modified Hockett-Sherby type law, which describes the dependence of the initial yield stress on temperature. A multi-step procedure is proposed, in combination with a gradient-based method, in order to enable the selection of an initial solution prone to lead to a feasible set of parameters. The identified parameters were used to perform the numerical analysis of the uniaxial tensile tests, taking into account the non-isothermal conditions, which occur in the Gleeble device. The analysis of these tests highlights that the non-isothermal conditions promote the increase of the strain rate in the centre of the specimen. However, the presence of the strain rate gradient along the specimen length seems to have a small impact in the classical analysis of the experimental data, as long as it is based on an effective gauge length that presents a uniform deformation.